Micro-nozzle flow and thrust prediction with high-density ratio using DSMC selection limiter - Frieler, T.; Groll, R. (Frontiers in Space Technologies, 2023)
Introduction: A Direct Simulation Monte Carlo (DSMC) solver with a modified collisional routine is used to investigate an argon gas flow through a millimeter-scaled thruster nozzle with high-density ratios. Method: The limiter scheme, denoted as the constant selection limiter (CSL), limits the possible number of selected collisional pairs to a constant value in accordance with the present simulation particles in the cell. Results: Results of the CSL scheme are compared with the experimental and numerical results of a compressible Navier–Stokes solver and discussed in comparison with baseline DSMC simulations. The influence of collision limitation by the CSL is discussed on the stagnation pressure of the thruster and on thrust and specific impulse prediction. The application of the limiter scheme makes the prediction of stagnation pressure challenging in some cases. Discussion: In contrast, thrust and specific impulse are predicted well, and their study remains valid. Investigated mass flow rates are 0.178 mg/s ≤ṁ≤ 71.360 mg/s, and flow Knudsen numbers below Kn = 0.01 and over Kn = 10 are present. Near atmospheric conditions are reached inside the thruster, generating pressure ratios up to 3,741 along the nozzle. The computational performance of the scheme is also discussed, and speed-up factors up to 0.51 are achieved.